Halal Certification Issues-Solutions in Indonesia: An Exploratory Study - Ismail; Nurhudawi; Kamaruddin; Jufri Naldo; Syahrial Arif Hutagalung (EKONOMIKA SYARIAH : Journal of Economic Studies, 2025)
This study aims to explore the problems and formulate solutions related to the implementation of halal certification for MSMEs in Indonesia. Employing a qualitative content analysis approach, ten articles published between 2019 and 2024 were analyzed using a mind map chart to identify key issues and integrated solutions. The findings highlight five major areas of concern: regulations, business actors, support systems, implementation processes, and public outreach. Key challenges include an underdeveloped legal structure, high certification costs, low awareness among business actors, and inadequate infrastructure and support. Proposed solutions involve offering free halal certification, enhancing outreach efforts, digitizing the certification system, strengthening institutional support, and providing technical assistance. This research offers a comprehensive mapping of problems and solutions, an approach not previously undertaken. It underscores the need for synergy between the government, support institutions, and MSMEs to build a more inclusive and effective halal certification ecosystem in Indonesia.   Penelitian ini bertujuan untuk mengeksplorasi problematika dan merumuskan solusi dalam pelaksanaan sertifikasi halal bagi pelaku UMKM di Indonesia. Dengan pendekatan analisis konten kualitatif, 10 artikel terpilih dari tahun 2019-2024 dianalisis menggunakan alat pemetaan mind maps chart untuk mengidentifikasi tantangan utama dan solusi yang terintegrasi. Hasil penelitian mengungkapkan lima aspek problematika utama: regulasi, pelaku usaha, sistem pendukung, implementasi, dan sosialisasi. Tantangan meliputi ketidaksiapan struktur hukum, biaya yang memberatkan, rendahnya kesadaran pelaku usaha, serta keterbatasan infrastruktur dan pendampingan. Solusi yang diusulkan meliputi program sertifikasi halal gratis, peningkatan sosialisasi, digitalisasi sistem, penguatan dukungan kelembagaan, dan pendampingan teknis. Penelitian ini berkontribusi dengan menyajikan pemetaan komprehensif problematika dan solusi tentang pelaksanaan sertifikasi halal bagi pelaku UMKM di Indonesia. Dalam implikasinya diperlukan sinergi antara pemerintah, lembaga pendukung, dan UMKM untuk menciptakan ekosistem sertifikasi halal yang lebih inklusif dan efisien di Indonesia.